EFFECTS OF AIR STONE WITH PLASTIC STRAW AS INTAKE CONNECTOR ON AERATION OF AQUACULTURE TANKS - AKPANITEAKU, R.C (Nigerian Journal of Fisheries, 2015)
Air stone used in this experiment was produced in the laboratory with river sand as the basic material. The air stone was comparatively tested with imported ones using a double-chambered air pump. Equal number (20 per m3) of mud crab (Potamon ebonyicum), tilapia (Oreochromis niloticus) and African cat fish (Clarias gariepinus) were used for the experiment. Air bubbles as small as those from the imported stone were observed on the locally produced one. More bubbles were observed on the local air stone than the imported one. Temperature of the test water fell within the tolerable range for aquaculture. Dissolved oxygen content also fell within adequate measurement. More crablets than the fish fingerlings survived after aerating the tanks, probably because of their hardy nature. More fingerlings of tilapia and African catfish (100% and 90% respectively) survived in the tanks aerated with imported air stone. While in the tanks aerated with locally produced stone, survival rates were 80% and 85% respectively. The percentage survival in the tanks aerated with locally produced air stone was quite significant (P < 0.05), and seemed to suggest that the accessory was safe and effective for aquaculture.